The genomics of microbe domestication - Testing the hypothesis of secondary domestication events in Saccharomyces cerevisiae - Pontes, Ana Patrícia Teixeira (2022)
For thousands of years microbes have been used, typically inadvertently, for the fermentation of a wide diversity of beverages and foods, which has led to the selection of relevant characteristics, thus promoting the domestication process. The yeast Saccharomyces cerevisiae is probably the most well-studied microbe with respect to domestication. However, most studies have been focused on a few industrially important lineages such as that of wine yeasts. Thus, this work aimed at deepening and extending the study of domestication trajectories in S. cerevisiae employing a broad perspective and using an integrated approach. For this, bioinformatic and experimental analyses were combined for a balanced perspective of genetic and phenotypic diversity of S. cerevisiae. In chapter 2, the emergence of a domesticated lineage associated with cachaça, and its relationship with wine yeasts was investigated. Our findings lead us to propose different domestication trajectories. We identified initial transitions from wild to domesticate, that gave rise to primary domesticated populations with specific traits related to the fermentation in which they were selected. We also identified secondarily domesticated populations that originate from primary domesticates that have been subjected to new and distinctive selective pressures. In chapter 3 we studied a population linked to wine yeasts but that arose after an inter-species hybridization. We analyzed in detail the consequences of an ancient hybridization between S. cerevisiae and S. paradoxus for adaptation to an anthropic environment. This study further highlighted the different layers of genomic and phenotypic transitions related to domestication and lead to the proposal of the concept of quasi-domesticate. Chapter 4 provided a comprehensive view of wild and domesticated populations of S. cerevisiae, integrating results from several recent publications. In that study, the distribution and ecology of wild populations was evaluated, and the evolution of certain genes that code for relevant phenotypic traits was investigated. The detailed study of domestication trajectories in S. cerevisiae carried out in this work revealed unanticipated levels of complexity, with cases of secondary domestication and of quasi-domestication. The results gathered in this project contribute to a better understanding of the mechanisms underpinning S. cerevisiae domestication. This will not only enable a better understanding the biology of this model organism from a fundamental perspective but will also be relevant for applied domains like the rational improvement of industrial fermentations.